The Role of Mobile Phones in Facilitating Business Education During the Transition to New Normal Learning Models - Tuliao, Romel C.; Santos, Angelo R.; Ortega, Sergiris A. (International Review of Management and Marketing, 2024)
This study explores the impact of mobile phone use on self-regulated learning among students at the Nueva Ecija University of Science and Technology San Isidro Campus, specifically within the College of Management and Business Technology. Using a descriptive correlational research design, the study aims to assess how integral mobile phones are to students’ learning processes, focusing on activities such as goal setting, environment structuring, task strategies, time management, help-seeking, and self-evaluation. Data were collected through a survey distributed to a significant portion of the student body, with subsequent statistical analysis to elucidate the relationship between mobile phone use and the efficacy of self-regulated learning strategies. Results reveal that mobile phones play a crucial role in enhancing students’ ability to manage their learning autonomously. They facilitate access to resources, enable communication with peers and instructors, and support various aspects of self-regulated learning. However, the study also identifies challenges such as distraction, dependency, and varying access to digital resources, suggesting a need for structured guidance in mobile usage. The assumptions emphasize the potential of mobile phones as beneficial educational tools when integrated with supportive measures to mitigate associated challenges. This study contributes to the understanding of mobile learning dynamics and underscores the need for educational strategies that leverage mobile technology effectively.